Motivational Barriers to Use Information and Communication Technology: Tribhuvan University Teacher’s Perception - Joshi, Bishnu Maya; Khatiwada, Shambhu Prasad (Tribhuvan University Journal, 2025)
The integration of Information and Communication Technology (ICT) into higher education has revolutionized teaching and learning, offering opportunities for greater engagement, innovative pedagogy, and efficient management of academic tasks. However, despite the growing digital infrastructure and policy emphasis on ICT, university teachers often encounter several barriers that hinder its effective utilization. Among these barriers, motivational issues stand out as significant factors impacting the willingness and readiness of educators to incorporate ICT into their professional routines. Understanding university teachers' perceptions of these motivational barriers is crucial to developing strategies that can foster a more supportive environment for ICT adoption. This study aims to examine the motivational barriers hindering ICT use among economics teachers at Tribhuvan University. Employing a quantitative research method with a descriptive research design, data were collected through a cross-sectional survey of 404 teachers using structured Likert scale questionnaires. Data were analyzed using both descriptive and inferential statistics. Mean, standard deviation, t-test and ANOVA were examined. Ethical considerations were taken into account throughout the research process. The study found significant barriers related to the absence of a teaching model, insufficient localized content, rigid schedules, lack of administrative support, and n ICT-friendly curriculum. Significant differences in barriers were observed based on campus category and level of education of teachers. Teachers in a community faced more substantial motivational barriers. Similarly, teachers with PhD and Post-Doc qualifications reported the higher motivational barriers compared to those with MPhil and master’s degrees. Addressing these barriers through increased support, curriculum development, localized content, professional development, and clear ICT policies is essential for effective ICT integration in higher education.